P088 TGFB bound to GARP promotes acetylation-mediated FOXP3 protein stabilisation. (21st February 2018) - Lehmkuhl, P; Zapp, B; Schulze-Koops, H; Skapenko, A
Abstract : Introduction: Regulatory T cells (Tregs) play a critical role in maintaining homeostasis and limiting autoimmunity. The transcription factor Forkhead box P3 (Foxp3) has been identified as the key regulator of Treg function and development. Its activity and stability are tightly regulated by acetylation dependent on the interplay between histone deacetylases (HDAC) and histone acetyltransferases (HAT). Tregs express distinctively on their cell surface glycoprotein A repetitions predominant (GARP). GARP binds latent TGFb and provides to Tregs an available pool of TGFb. The function of this TGFb source for Tregs has not been investigated yet. Treg-derived TGFb might on the one hand be involved in mediating suppressive functions of Tregs and on the other hand be important for maintaining Treg homeostasis. Objectives: To analyse the function of surface TGFb bound to GARP utilising GARP-deficient Tregs from conditional CD4 specific GARP knockout mice. Methods: CD4 positive CD25 +or CD25- T cell from GARP-deficient or wild type mice were purified using MACS separation and stimulated with anti-CD3 and anti-CD28 in the presence or absence of TGFb for different times. mRNA expression profile was evaluated in non-stimulated and stimulated cells by Affymetrix gene array analysis and confirmed by real-time PCR. Acetylation, Foxp3 protein expression and Smad2/3 phosphorylation were assessed by intracellular flow cytometry. Half-life of Foxp3 was evaluated in cell cultures using cycloheximid. Acetylation of Foxp3 was determined by fluorescence resonance energy transfer (FRET) utilising a FRET antibody pair for Foxp3 and acetylated lysine. The regulatory capacity of Treg was assessed in vivo in reconstitution experiments of Rag-deficient mice with CD25- CD4 T cells or bone marrow cells. Results: GARP-deficient Tregs exhibited a markedly diminished intracellular protein acetylation. Acetylation of Foxp3 was also significantly lower. Consistently, expression of a Treg specific HDAC, HDAC9, was up regulated in Tregs lacking GARP. Both acetylation and HDAC9 expression levels could be restored by addition of exogenous TGFb. In this regard basal phosphorylation of TGFb-dependent transcription factors Smad2/3 was diminished in Tregs lacking GARP. Further analysis revealed an unstable phenotype of GARP-deficient Tregs characterised by a shorter half-life of Foxp3, a faster loss of Foxp3 in response to anti-CD3/28 stimulation and restricted regulatory capacity. Conclusions: Lack of GARP on the cell surface results in a reduced TGFb availability and in a decreased TGFb signalling in CD4 Tregs. Diminished TGFb signalling leads in turn to an elevated HDAC9 expression and to a decreased Foxp3 acetylation. Lower acetylated Foxp3 determines an instable phenotype of GARP-deficient Tregs and their failure to proper regulate an immune reaction. Acknowledgements: This work supported by DFG grants SK59/09–1 and Schu1683/10–1, and by BMBF Projekt Arthromark 01Ec1401B. Disclosure of interest: None declared